Pouring Tea For Therapy To Improve Physical Mobility In Lumbal Back Pain Patients - tanta, Pak; Hasbi, Habid AL; Sarwoko; Bahri, Ahmad Syamsul; Rismawati (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
Old resources are a gift from God Almighty so that they can be used as well as possible for the benefit of many people. It is hoped that natural resources can be used for all levels of society, both those who are healthy and those experiencing health problems/deterioration. Likewise, using raw data sources can increase people's income so the economy rises. It is essential to utilize natural resources with various innovations that are needed for the benefit of the surrounding community, ranging from health, recreation, or culinary. Kebakan Hamlet, Metuk Village, has abundant natural water resources that have yet to be used optimally to improve the residents' economy and health. Residents only use natural resources for bathing, washing, and irrigation. The existing natural resources have made swimming pools for therapy for low back pain sufferers so that visitors who come for treatment can have a more positive impact on the surrounding community by opening food stalls, renting out floats or parking so that the existence of the pool can be beneficial from a health perspective. And economic value for local residents